Diagenesis and reservoir quality evolution of the paleogene sokor1 sandstones in the agadem block, termit basin, eastern Niger - ADA Moussa, HAMMA; Harouna, MOUSSA (International Journal of Advanced Geosciences, 2019)
The Paleogene Sokor1 Formation in Termit Basin is recognized as the most important hydrocarbon reservoir. However, in spite of its reservoir importance, published studies on its diagenetic process and their effects on reservoir quality are absent or limited. Petrographic analysis, scanning electron microscopy and X-ray diffraction were used to assess diagenetic characteristics, controls on reservoir and reservoir quality of Sokor1 Formation. The Sokor1 sandstones are mostly quartz sandstone, lithic quartz-arenite and rarely lithic fedspathic-quartz-arenite, with an average mass fraction of quartz 95%, feldspar 1.6% and rock fragments 3.4% (Q95F1.6R3.4). Diagenetic processes in Sokor1 sandstones include mechanical compaction, cementation, dissolution and replacement. The main authigenic minerals are quartz overgrowth and clay minerals, which occur as pore-filling and pore-lining cements. Sokor1 sandstone has undergone stages A and B of eodiagenesis and now, it is experiencing stage A of mesodiagenesis. The widespread occurrences of quartz overgrowth suggest that Sokor1 sandstones lost a significant amount of primary porosity during its diagenetic history. Secondary porosity occurred due to partial and complete dissolution of feldspar, quartz grains and rock fragments, so increasing reservoir quality. The latter is predominantly controlled by depositional environment controls on grains size, sorting and matrix. Thus, reservoirs of best quality were deposited in braided river channel environments. In addition, oil accumulation has no discernable effects on porosity and oil probably entered the reservoir at late diagenetic stage, after quartz overgrowth and authigenic cements had already occurred.Â Â